Statistical Analysis of Mortality and Morbidity Due to Traffic Accidents in Iraq (Journal of Engineering, 2018)
Undoubtedly, Road Traffic Accidents (RTAs) are a major dilemma in term of mortality and morbidity facing the road users as well as the traffic and road authorities. Since 2002, the population in Iraq has increased by 49 percent and the number of vehicles by three folds. Consequently, these increases were unfortunately combined with rising the RTAs number, mortality and morbidity. Alongside the humanitarian tragedies, every year, there are considerable economic losses in Iraq lost due to the epidemic of RTAs. Given the necessity of understanding the contributory factors related to RTAs for the implementation by traffic and road authorities to improve the road safety, the necessity have been a rise for this research which focuses into two objectives; the first objective is a descriptive analysis for the RTA based on a retrospective analysis during the period of 2002–2015 with the aids of the data obtained from the reports of Iraqi Central Statistical Organization whereas the second objective is to conduct a statistical analysis for RTAs to correlate the criterion variable of accident number, mortality or morbidity to predictor variable which include motorization level or population using traditional statistical regression approach and Artificial Neural Network (ANN) approach.